Pyridine resin as well as preparation method and application thereof
Through the preparation method of pyridine resin, the chloromethylation and pyridine functionalization of crosslinked microspheres of styrene skeleton copolymers are used to solve the problem of poor selectivity of uranium adsorption in the existing ion exchange resin, and the efficient uranium adsorption effect is achieved.
Patent Information
- Application Number
- CN202411903849.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing ion exchange resins have poor adsorption selectivity to uranium, resulting in unsatisfactory adsorption capacity and adsorption efficiency, making it difficult to effectively treat uranium-containing wastewater.
The pyridine resin was prepared by the preparation method of pyridine resin, and the pyridine functionalization of crosslinked microspheres of styrene skeleton copolymer were prepared with good uranium adsorption capacity.
When pyridine resin adsorbs uranium in acidic uranium-containing solution, the adsorption rate reaches more than 95%, which significantly improves the adsorption capacity and adsorption efficiency of uranium.
Smart Images

Figure CN119708319A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a pyridine resin and a preparation method and application thereof. Background Art
[0002] The uranium mining process and the industrial uranium extraction process produce a large amount of uranium-containing wastewater, with uranium concentrations reaching 10-100 mg / L. Uranium is radioactive and chemically toxic, and if it is allowed to be discharged into the environment, it will cause serious harm.
[0003] At present, the methods for treating uranium-containing wastewater include ion exchange, chemical precipitation, evaporation concentration, membrane separation and biochemical methods. Among them, ion exchange is a relatively efficient, economical and reliable method. The principle of ion exchange is that when ion exchange resin comes into contact with radioactive wastewater, the exchangeable functional groups on the resin interact with the uranium ions in the wastewater and adsorb them onto the resin, thereby achieving the purpose of removing uranium ions from the wastewater. Ion exchange resin is a polymer electrolyte with a three-dimensional network structure with functional groups. Its advantages are large processing capacity, high adsorption capacity, ability to remove various ions, repeated regeneration and long working life.
[0004] However, since the functional groups of existing ion exchange resins have low adsorption selectivity for uranium, the adsorption capacity and efficiency of ion exchange resins for uranium are not ideal. Summary of the invention
[0005] In view of this, one object of the present invention is to provide a method for preparing a pyridine resin. The prepared pyridine resin has good uranium adsorption capacity. Another object of the present invention is to provide a pyridine resin prepared by the above preparation method. Another object of the present invention is to provide the use of the above pyridine resin.
[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0007] In one aspect, the present invention provides a method for preparing a pyridine resin, comprising the following steps:
[0008] 1) mixing styrene, divinylbenzene, an initiator and a porogen to form an organic phase, adding the organic phase to a dispersant solution, reacting at 50 to 95° C., and obtaining styrene skeleton copolymer cross-linked microspheres;
[0009] The weight of the divinylbenzene is 6-20wt% of the total weight of styrene and divinylbenzene; the weight of the initiator is 0.1-2wt% of the total weight of styrene and divinylbenzene; the ratio of the weight of the porogen to the total weight of styrene and divinylbenzene is (0.1-1):1; the ratio of the weight of the dispersant solution to the weight of the organic phase is (1-6):1;
[0010] 2) Swelling the styrene skeleton copolymer cross-linked microspheres obtained in step 1), then adding a Lewis acid catalyst, reacting at 30-90° C. to obtain chloromethylated cross-linked microspheres; wherein the weight ratio of the Lewis acid catalyst to the styrene skeleton copolymer cross-linked microspheres is (0.1-0.5):1;
[0011] 3) Swelling the chloromethylated cross-linked microspheres obtained in step 2), then adding pyridine and an acid binding agent, reacting at 50-90° C. to obtain a pyridine resin; wherein the weight ratio of the pyridine to the chloromethylated cross-linked microspheres is (3-6):1; the weight ratio of the acid binding agent to the chloromethylated cross-linked microspheres is (0.05-0.5):1.
[0012] According to one embodiment of the present invention, preferably, in step 1), the dispersant solution may be an aqueous dispersant solution, and the mass concentration of the aqueous dispersant solution is 0.2 to 5 wt %, preferably 0.5 to 2 wt %.
[0013] The dispersant may be selected from at least one of polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polyethylene glycol, sodium lauryl sulfate, carboxymethyl cellulose, and carboxypropyl methyl cellulose; preferably at least one of polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, and sodium lauryl sulfate.
[0014] According to one embodiment of the present invention, preferably, the preparation method of the dispersant solution is:
[0015] Add the dispersant to the solvent and heat until the dispersant is completely dissolved.
[0016] The heating temperature may be 40 to 90° C., preferably 50 to 80° C. The heating time may be 0.5 to 3 h, preferably 1 to 2 h.
[0017] According to the preparation method of the present invention, preferably, in step 1), the initiator is selected from at least one of benzoyl peroxide and azobisisobutyronitrile; preferably benzoyl peroxide or azobisisobutyronitrile. The porogen is selected from at least one of liquid paraffin and petroleum ether; preferably liquid paraffin or petroleum ether.
[0018] In step 1), styrene is used as a monomer and divinylbenzene is used as a crosslinking agent. The weight of the divinylbenzene can be 6-20wt% of the total weight of styrene and divinylbenzene; preferably 9-18wt%. The weight of the initiator can be 0.1-2wt% of the total weight of styrene and divinylbenzene; preferably 0.5-1.5wt%. The ratio of the weight of the porogen to the total weight of styrene and divinylbenzene can be (0.1-1):1; preferably (0.5-1):1. The ratio of the weight of the dispersant solution to the weight of the organic phase can be (1-8):1; preferably (2-6):1.
[0019] In step 1), the reaction is a curing reaction, and the reaction temperature may be 50 to 95° C., preferably 60 to 90° C. The reaction time may be 6 to 20 hours, preferably 8 to 18 hours.
[0020] According to one embodiment of the present invention, after the reaction in step 1) is completed, the product can be boiled at 100° C. and dried to obtain styrene skeleton copolymer cross-linked microspheres.
[0021] In the present invention, the boiling time can be 1 to 5 hours, preferably 2 to 3 hours. The drying temperature can be 50 to 95° C., preferably 60 to 90° C.; the drying time can be 1 to 5 hours, preferably 2 to 4 hours.
[0022] In step 1), controlling the ratio of the reaction raw materials and the reaction conditions within the above range is conducive to the curing reaction and is more conducive to the generation of qualified styrene skeleton copolymer cross-linked microspheres.
[0023] According to the preparation method of the present invention, preferably, in step 2), the Lewis acid catalyst is selected from at least one of FeCl3, TiCl4, ZnCl2, and AlCl3; preferably at least one of FeCl3, ZnCl2, and AlCl3.
[0024] In the present invention, the weight ratio of the Lewis acid catalyst to the styrene skeleton copolymer cross-linked microspheres may be (0.1-0.5):1; preferably (0.2-0.5):1.
[0025] According to the preparation method of the present invention, preferably, in step 2), chloromethyl ether is used to swell the styrene skeleton copolymer cross-linked microspheres obtained in step 1). The weight ratio of chloromethyl ether to the styrene skeleton copolymer cross-linked microspheres can be (2-8):1, preferably (3-6):1.
[0026] In step 2), the time for swelling the styrene skeleton copolymer cross-linked microspheres obtained in step 1) with chloromethyl ether can be 1 to 5 hours, preferably 1 to 3 hours.
[0027] In step 2), the reaction is a reflux reaction, which can be carried out in any reflux reaction device known in the art. The reaction temperature can be 30 to 90° C., preferably 40 to 80° C. The reaction time can be 8 to 36 hours, preferably 10 to 30 hours.
[0028] According to one embodiment of the present invention, after the reaction in step 2) is completed, the product may be washed with an aqueous solution of a C1-C5 alkyl alcohol and dried to obtain chloromethylated cross-linked microspheres.
[0029] In the present invention, the C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol, preferably at least one of methanol and ethanol. The volume ratio of the C1-C5 alkyl alcohol to water can be 1:2 to 2:1, preferably 1:1.
[0030] The drying is vacuum drying, the drying temperature can be 30 to 90° C., preferably 45 to 85° C.; the drying time can be 1 to 5 hours, preferably 2 to 4 hours.
[0031] In step 2), the ratio of the reaction raw materials and the reaction conditions are controlled within the above range, which is beneficial to the reaction and more conducive to the substitution of chloromethyl groups to generate qualified chloromethylated cross-linked microspheres.
[0032] According to the preparation method of the present invention, preferably, in step 3), the chloromethylated cross-linked microspheres prepared in step 1) are swollen with C1-C5 alkyl alcohol. The weight ratio of C1-C5 alkyl alcohol to chloromethylated cross-linked microspheres can be (2-6):1, preferably (3-5):1.
[0033] In step 3), the chloromethylated cross-linked microspheres prepared in step 2) are swollen with C1-C5 alkyl alcohol for 1-5 hours, preferably 1-3 hours.
[0034] In the present invention, the C1-C5 alkyl alcohol may be a C1-C3 normal alkyl alcohol; preferably at least one of methanol and ethanol.
[0035] According to the preparation method of the present invention, preferably, the acid binding agent is selected from at least one of triethylamine, anhydrous sodium carbonate, anhydrous potassium carbonate and anhydrous sodium acetate; preferably at least one of triethylamine and anhydrous sodium carbonate.
[0036] In the present invention, the weight ratio of the acid binding agent to the methylated cross-linked microspheres may be (0.05-0.5):1; preferably (0.1-0.3):1.
[0037] In the present invention, the weight ratio of pyridine to chloromethylated cross-linked microspheres may be (3-6):1; preferably (3-5):1.
[0038] In step 3), the reaction temperature may be 50 to 90° C., preferably 60 to 80° C. The reaction time may be 8 to 24 hours, preferably 10 to 20 hours.
[0039] According to one embodiment of the present invention, after the reaction in step 3) is completed, the product may be washed and dried to obtain a pyridine resin.
[0040] In step 3), washing can be performed using an aqueous solution of a C1-C5 alkyl alcohol. The washing times can be 1 to 5 times, preferably 3 to 4 times. The drying can be performed using any drying method known in the art; preferably, vacuum drying is performed at 30 to 60° C. for 1 to 5 hours.
[0041] The C1-C5 alkyl alcohol is a C1-C3 normal alkyl alcohol, preferably at least one of methanol and ethanol. The volume ratio of the C1-C5 alkyl alcohol to water can be 1:2 to 2:1, preferably 1:1.
[0042] In step 3), controlling the ratio of the reaction raw materials and the reaction conditions within the above range is beneficial to the reaction and is more conducive to the pyridine functionalization of the chloromethylated cross-linked microspheres to generate qualified pyridine resin.
[0043] In the present invention, the water used in the preparation method can be deionized water or ultrapure water, preferably deionized water.
[0044] On the other hand, the present invention also provides a pyridine resin prepared by the above preparation method.
[0045] The pyridine resin has a ball penetration rate of at least 97%, preferably at least 97.2%. The pyridine resin has an adsorption rate of at least 95% for uranium in an acidic uranium-containing solution, preferably at least 99%.
[0046] Pyridine resin has good uranium adsorption capacity when adsorbing uranium in acidic uranium-containing solution.
[0047] In another aspect, the present invention also provides the use of the pyridine resin in removing uranium from acidic uranium-containing wastewater.
[0048] The acidic uranium-containing wastewater may be acidic uranium-containing industrial wastewater; preferably, acidic uranium-containing industrial wastewater having a pH value of ≤5.
[0049] The present invention successfully grafts pyridine functional groups onto a resin skeleton by using suspension polymerization and chemical modification methods to prepare a pyridine resin. The pyridine resin has good wear resistance and mechanical properties and has a good adsorption effect on uranium in acidic uranium-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1This is an infrared spectrum of the chloromethylated cross-linked microspheres and pyridine resin prepared in Example 1 of the present invention; wherein the chlorospheres represent the chloromethylated cross-linked microspheres. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0052] <Test Method>
[0053] Uranium adsorption capacity test
[0054] Take 0.2 g of the prepared pyridine resin and carry out a static adsorption test in 100 mL of uranyl nitrate adsorption stock solution with a pH value of 1. The adsorption time is 6 h. The uranyl ion concentration in the adsorption stock solution and the uranyl ion concentration in the adsorption tail solution after adsorption are determined.
[0055] The uranyl ion concentration was determined according to GB / T11225-1989.
[0056] Determination of the ball rate of infiltration grinding
[0057] Take 50 g of the prepared pyridine resin and measure the infiltration and grinding sphericity of the resin according to GB / T 12598-2001.
[0058] Elemental analysis characterization
[0059] Various EL / micro cube element analyzers produced by Elementar were used for detection.
[0060] Infrared spectroscopy characterization
[0061] The Tensor II infrared spectrometer produced by Bruker, Germany, was used at a wave number of 4000-400 cm -1 Detection within the range.
[0062] <Ingredients>
[0063] Unless otherwise specified, the raw materials used in the following examples are all commercially available products.
[0064] Example 1
[0065] 1. Preparation of styrene skeleton copolymer cross-linked microspheres
[0066] 8 g of polyvinyl alcohol was added into 400 mL of deionized water, and heated at 60° C. for 1 h to dissolve all the polyvinyl alcohol, thereby obtaining a polyvinyl alcohol aqueous solution.
[0067] Take 34.92g of styrene, 5.08g of divinylbenzene, 0.6g of benzoyl peroxide and 40g of petroleum ether, mix them evenly, and use them as the organic phase. Add the organic phase to the above polyvinyl alcohol aqueous solution, stir to form beads, and heat at 85°C for 12 hours to perform a curing reaction. After the reaction is completed, boil the reaction product in 100°C water for 2 hours, filter and dry the reaction product at 80°C for 4 hours to obtain styrene skeleton copolymer cross-linked microspheres.
[0068] 2. Preparation of chloromethylated cross-linked microspheres
[0069] Take 20g of styrene skeleton copolymer cross-linked microspheres, add 100g of chloromethyl ether to fully swell for 2h, then add 8g of zinc chloride, and stir and heat at 50°C for 16h for reflux reaction. After the reaction is completed, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and after washing, vacuum dry the reaction product at 50°C for 3h to obtain chloromethylated cross-linked microspheres.
[0070] 3. Preparation of pyridine resin
[0071] Take 20g of chloromethylated cross-linked microspheres, add 60g of anhydrous methanol to fully swell for 2h, then add 60g of pyridine and 3g of triethylamine, and stir and heat at 80°C for 14h to react. After the reaction, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain pyridine resin.
[0072] Example 2
[0073] 1. Preparation of styrene skeleton copolymer cross-linked microspheres
[0074] 8 g of polyvinyl alcohol was added into 400 mL of deionized water, and heated at 60° C. for 1 h to dissolve all the polyvinyl alcohol, thereby obtaining a polyvinyl alcohol aqueous solution.
[0075] Take 33.66g of styrene, 6.34g of divinylbenzene, 0.6g of benzoyl peroxide and 40g of petroleum ether, mix them evenly, and use them as the organic phase. Add the organic phase to the above polyvinyl alcohol aqueous solution, stir to form beads, and heat at 85°C for 12 hours to perform a curing reaction. After the reaction is completed, boil the reaction product in 100°C water for 2h, filter and dry the reaction product at 80°C for 4h to obtain styrene skeleton copolymer cross-linked microspheres.
[0076] 2. Preparation of chloromethylated cross-linked microspheres
[0077] Take 20g of styrene skeleton copolymer cross-linked microspheres, add 120g of chloromethyl ether to fully swell for 2h, then add 10g of zinc chloride, stir and heat at 50°C for 24h for reflux reaction. After the reaction is completed, wash the reaction product 3 times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain chloromethylated cross-linked microspheres.
[0078] 3. Preparation of pyridine resin
[0079] Take 20g of chloromethylated cross-linked microspheres, add 60g of anhydrous methanol to fully swell for 2h, then add 80g of pyridine and 4g of anhydrous sodium carbonate, and stir and heat at 80°C for 18h to react. After the reaction, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain pyridine resin.
[0080] Comparative Example 1
[0081] 1. Preparation of styrene skeleton copolymer cross-linked microspheres
[0082] 1 g of polyvinyl alcohol was added into 200 mL of deionized water and heated at 60° C. for 1 h to dissolve all the polyvinyl alcohol, thereby obtaining a polyvinyl alcohol aqueous solution.
[0083] Take 48.22g of styrene, 5.07g of divinylbenzene, 0.27g of benzoyl peroxide and 26.7g of liquid paraffin, mix them evenly, and use them as the organic phase. Add the organic phase to the above polyvinyl alcohol aqueous solution, stir to form beads, and heat at 85°C for 12 hours to perform a curing reaction. After the reaction is completed, boil the reaction product in 100°C water for 2h, filter and dry the reaction product at 80°C for 4h to obtain styrene skeleton copolymer cross-linked microspheres.
[0084] 2. Preparation of chloromethylated cross-linked microspheres
[0085] Take 20g of styrene skeleton copolymer cross-linked microspheres, add 60g of chloromethyl ether to fully swell for 2h, then add 4g of ferric chloride, stir and heat at 50°C for 12h for reflux reaction. After the reaction is completed, wash the reaction product 3 times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain chloromethylated cross-linked microspheres.
[0086] 3. Preparation of pyridine resin
[0087] Take 20g of chloromethylated cross-linked microspheres, add 60g of anhydrous ethanol to fully swell for 2h, then add 40g of pyridine and 2g of anhydrous sodium carbonate, and stir and heat at 60°C for 10h to react. After the reaction, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain pyridine resin.
[0088] Comparative Example 2
[0089] 1. Preparation of styrene skeleton copolymer cross-linked microspheres
[0090] 3 g of polyvinyl alcohol was added into 300 mL of deionized water and heated at 60° C. for 1 h to dissolve all the polyvinyl alcohol, thereby obtaining a polyvinyl alcohol aqueous solution.
[0091] Take 46.53g of styrene, 6.76g of divinylbenzene, 0.53g of azobisisobutyronitrile and 26.7g of petroleum ether, mix them evenly, and use them as the organic phase. Add the organic phase to the above polyvinyl alcohol aqueous solution, stir to form beads, and heat at 85°C for 12 hours to perform a curing reaction. After the reaction is completed, boil the reaction product in 100°C water for 2 hours, filter and dry the reaction product at 80°C for 4 hours to obtain styrene skeleton copolymer cross-linked microspheres.
[0092] 2. Preparation of chloromethylated cross-linked microspheres
[0093] Take 20g of styrene skeleton copolymer cross-linked microspheres, add 80g of chloromethyl ether to fully swell for 2h, then add 6g of aluminum chloride, stir and heat at 50°C for 12h for reflux reaction. After the reaction is completed, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then vacuum dry the reaction product at 50°C for 3h to obtain chloromethylated cross-linked microspheres.
[0094] 3. Preparation of pyridine resin
[0095] Take 20g of chloromethylated cross-linked microspheres, add 60g of anhydrous methanol to fully swell for 2h, then add 40g of pyridine and 2g of triethylamine, and stir and heat at 60°C for 10h to react. After the reaction, wash the reaction product three times with methanol aqueous solution (methanol to deionized water volume ratio of 1:1), and then dry the reaction product under vacuum at 50°C for 3h to obtain pyridine resin.
[0096] Experimental example 1
[0097] 0.2 g of each of the styrene skeleton copolymer cross-linked microspheres, chloromethylated cross-linked microspheres and pyridine resin prepared in Example 1 were weighed and measured for elemental analysis and characterization. The results are shown in Table 1.
[0098] Table 1
[0099]
[0100]
[0101] As shown in Table 1, compared with the styrene skeleton copolymer cross-linked microspheres, the contents of C and H elements in the chloromethylated cross-linked microspheres are reduced, and the Cl content of the chloromethylated cross-linked microspheres increases to 21.4wt%, proving that the chloromethylation reaction proceeds normally. Compared with the chloromethylated cross-linked microspheres, the N element content of the pyridine resin is significantly increased, proving that the pyridine group has been successfully grafted onto the resin.
[0102] 0.1 g of the chloromethylated cross-linked microspheres and pyridine resin prepared in Example 1 were taken respectively, and infrared spectroscopy was directly performed without tableting. The results are as follows: Figure 1 shown.
[0103] Depend on Figure 1 It can be seen that there is a significant difference between the two curves. In the infrared curve of pyridine resin, at the wave number 1264cm -1 With 670cm -1 The peak at wave number 1360cm -1 The stretching vibration of CN appears at the position, indicating that pyridine undergoes a substitution reaction with the -Cl in the chloromethylated cross-linked microspheres (chlorine balls) to form pyridine resin.
[0104] Experimental Example 2
[0105] The pyridine resins prepared in Examples 1-2 and Comparative Examples 1-2 were tested for their roundness by grinding. The results are shown in Table 2.
[0106] Table 2
[0107] serial number Grinding ball rate (%) Example 1 97.4 Example 2 98.2 Comparative Example 1 93.7 Comparative Example 2 95.8
[0108] It can be seen from Table 2 that the grinding ball rate of the pyridine resin prepared in the example is higher than that of the comparative example, which indicates that the pyridine resin prepared in the example has better wear resistance and mechanical properties.
[0109] The uranium adsorption capacity of the pyridine resins prepared in Examples 1-2 and Comparative Examples 1-2 was tested respectively. The specific parameters and test results are shown in Table 3.
[0110] Table 3
[0111]
[0112]
[0113] It can be seen from Table 3 that the adsorption capacity of the pyridine resin prepared in the example is significantly higher than that of the comparative example when adsorbing uranium ions in the acidic uranium-containing solution.
[0114] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a pyridine resin, comprising the following steps: 1) mixing styrene, divinylbenzene, an initiator and a porogen to form an organic phase, adding the organic phase to a dispersant solution, reacting at 50 to 95° C., and obtaining styrene skeleton copolymer cross-linked microspheres; The weight of divinylbenzene is 6-20wt% of the total weight of styrene and divinylbenzene; the weight of the initiator is 0.1-2wt% of the total weight of styrene and divinylbenzene; the ratio of the weight of the porogen to the total weight of styrene and divinylbenzene is (0.1-1):1; the ratio of the weight of the dispersant solution to the weight of the organic phase is (1-8):1; 2) Swelling the styrene skeleton copolymer cross-linked microspheres obtained in step 1), then adding a Lewis acid catalyst, reacting at 30-90° C. to obtain chloromethylated cross-linked microspheres; wherein the weight ratio of the Lewis acid catalyst to the styrene skeleton copolymer cross-linked microspheres is (0.1-0.5):1; 3) Swelling the chloromethylated cross-linked microspheres obtained in step 2), then adding pyridine and an acid binding agent, reacting at 50-90° C. to obtain a pyridine resin; wherein the weight ratio of the pyridine to the chloromethylated cross-linked microspheres is (3-6):1; the weight ratio of the acid binding agent to the chloromethylated cross-linked microspheres is (0.05-0.5):
1.
2. The preparation method according to claim 1, characterized in that: In step 1), the dispersant solution is an aqueous dispersant solution, and the mass concentration of the aqueous dispersant solution is 0.2 to 5 wt %; The dispersant is selected from at least one of polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polyethylene glycol, sodium lauryl sulfate, carboxymethyl cellulose and carboxypropyl methyl cellulose.
3. The preparation method according to claim 1, characterized in that: In step 1), the initiator is selected from at least one of benzoyl peroxide and azobisisobutyronitrile; the porogen is selected from at least one of liquid paraffin and petroleum ether.
4. The preparation method according to claim 1, characterized in that: In step 2), the Lewis acid catalyst is selected from at least one of FeCl3, TiCl4, ZnCl2, and AlCl3.
5. The preparation method according to claim 1, characterized in that: In step 2), the styrene skeleton copolymer cross-linked microspheres obtained in step 1) are swollen with chloromethyl ether.
6. The preparation method according to claim 1, characterized in that: In step 3), the chloromethylated cross-linked microspheres obtained in step 1) are swollen with C1-C5 alkyl alcohol.
7. The preparation method according to claim 1, characterized in that: In step 3), the acid binding agent is selected from at least one of triethylamine, anhydrous sodium carbonate, anhydrous potassium carbonate and anhydrous sodium acetate.
8. The preparation method according to claim 1, characterized in that: In step 1), the reaction time is 6 to 20 hours; In step 2), the reaction time is 8 to 36 hours; In step 3), the reaction time is 8 to 24 hours.
9. A pyridine resin prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The infiltration and grinding ball rate of the pyridine resin is at least 97%; the adsorption rate of the pyridine resin on uranium in the acidic uranium-containing solution is at least 95%.
10. Use of the pyridine resin according to claim 9 in removing uranium from acidic uranium-containing wastewater.
Citation Information
Patent Citations
Preparation method of aminopyridine modified resin adsorbing material
CN103588912A
Uranium adsorption resin
CN105399888A
Preparation method of uranium-adsorbing narrow-particle-size-distribution strong-basicity resin
CN113501901A
Crosslinked polystyrene resin as well as preparation method and application thereof
CN114478851A
Pyridyl modified composite function super high crosslinked adsorptive resin and its preparing method
CN1858088A